Comorbidity Influences the Comparative Safety of Biologic Therapy in Older Adults With Inflammatory Bowel Diseases. (12th November 2022) - Cheng, David; Kochar, Bharati; Cai, Tianxi; Ritchie, Christine S.; Ananthakrishnan, Ashwin N.
Abstract : INTRODUCTION: There are limited data on comparative risk of infections with various biologic agents in older adults with inflammatory bowel diseases (IBDs). We aimed to assess the comparative safety of biologic agents in older IBD patients with varying comorbidity burden. METHODS: We used data from a large, national commercial insurance plan in the United States to identify patients 60 years and older with IBD who newly initiated tumor necrosis factor-α antagonists (anti-TNF), vedolizumab, or ustekinumab. Comorbidity was defined using the Charlson Comorbidity Index (CCI). Our primary outcome was infection-related hospitalizations. Cox proportional hazards models were fitted in propensity score-weighted cohorts to compare the risk of infections between the different therapeutic classes. RESULTS: The anti-TNF, vedolizumab, and ustekinumab cohorts included 2, 369, 972, and 352 patients, respectively, with a mean age of 67 years. The overall rate of infection-related hospitalizations was similar to that of anti-TNF agents for patients initiating vedolizumab (hazard ratio [HR] 0.94, 95% confidence interval [CI] 0.84–1.04) and ustekinumab (0.92, 95% CI 0.74–1.16). Among patients with a CCI of >1, both ustekinumab (HR: 0.66, 95% CI: 0.46–0.91, p-interaction <0.01) and vedolizumab (HR: 0.78, 95% CI: 0.65–0.94, p-interaction: 0.02) were associated with a significantly lower rate of infection-related hospitalizations compared with anti-TNFs. No difference was found among patients with a CCI of ≤1. DISCUSSION: Among adults 60 years and older with IBD initiating biologic therapy, both vedolizumab and ustekinumab were associated with lower rates of infection-related hospitalizations than anti-TNF therapy for those with high comorbidity burden.